2002
DOI: 10.1177/154405910208100112
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota of Young Children from Tooth and Tongue Samples

Abstract: This study determined the frequency with which 38 microbial species were detected in 171 randomly selected children from 6 to 36 months of age. Children were sampled and dental caries measured. Oral samples were assayed by means of a checkerboard DNA probe assay. The detection frequencies from tongue samples in children under 18 mos were: S. mutans 70%, S. sobrinus 72%, P. gingivalis 23%, B. forsythus 11%, and A. actinomycetemcomitans 30%, with similar detection frequencies in children over 18 mos. Thus, S. mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
73
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 24 publications
8
73
2
6
Order By: Relevance
“…However, this site was not representative of all genotypes detected in the children's oral cavities. Tanner et al (33) found that species detection from tooth and tongue samples was highly associated, with most species detected more frequently from tongue samples than from tooth samples in children younger than 18 months of age. This agrees with our finding that several geno- g The chi-square test showed significant statistical difference among the numbers of strains isolated from dental plaque and the other three sites (D ϫ S, D ϫ T, and D ϫ G) (P ϭ 0.0000).…”
Section: Discussionmentioning
confidence: 99%
“…However, this site was not representative of all genotypes detected in the children's oral cavities. Tanner et al (33) found that species detection from tooth and tongue samples was highly associated, with most species detected more frequently from tongue samples than from tooth samples in children younger than 18 months of age. This agrees with our finding that several geno- g The chi-square test showed significant statistical difference among the numbers of strains isolated from dental plaque and the other three sites (D ϫ S, D ϫ T, and D ϫ G) (P ϭ 0.0000).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, they contain a composite of all the necessary microorganisms for either localized health or endogenous disease (72). They are continuously bathed in saliva and subjected to the oral functions of mastication and swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies based on microbiological and immunological findings have classified P. gingivalis as one of the causative agents in periodontitis (25,36). However, P. gingivalis is also found as part of the indigenous supra-and subgingival microflora in healthy individuals of all ages (40,47,48). During colonization of the oral tissues, P. gingivalis is exposed to various oxidative stress conditions (e.g., during survival in saliva) in which the presence of an unfavorable redox potential and the damaging effects of reactive oxygen species (ROS) might challenge its survival before finding the appropriate anaerobic microenvironment in which to establish itself and proliferate.…”
mentioning
confidence: 99%